The influence of nanoparticles of modifiers on the kinetics of transformation of high-strength low-alloy steels in metal welds - Grigorenko, G. M.; Kostin, V. A.; Golovko, V. V.; Zhukov, V. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
The structure of welds of 14KhGNDTs high-strength low-alloy steel is studied. In the melt of this steel, nanopowder particles of various refractory compounds such as oxides, nitrides, and carbides (TiC, TiN, SiC, VC, NbC, TiO2, Al2O3, MgO, ZrO2) were introduced. The studies have shown the efficiency of the use of nanooxides TiO2 and ZrO2, which allows us to improve the mechanical properties of the metal of welds (σv = 708 and 621 MPa, respectively, KCV−20 = 60 and 72.9 J/cm2, δ = 21 and 19%) due to the formation of a complex of bainite and acicular structures. With the aid of a Gleeble 3800 installation imitating the thermal cycles, the relationship between the temperature intervals of the transformation, number of structural components, and type of modifying nanoparticles is established.